Content Marketing and E-WOM as Drivers of Purchase Intention: Evidence from Erigo on TikTok Shop - Setianingsih, Rita Eka; Dema, Yosef (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
In an era where scrolling replaces strolling and purchases are made with a tap, this study dives into the digital vortex to examine how content marketing and electronic word of mouth (E-WOM) shape the purchase intention of consumers toward Erigo, a rising local fashion brand, on TikTok Shop in Jakarta. As short-form video platforms redefine brand-consumer interaction, especially among digital-native youth, understanding the psychological triggers behind their buying behavior becomes paramount. Anchored in the Elaboration Likelihood Model (ELM) and the Theory of Planned Behavior (TPB), this research employs a quantitative approach with data from 103 purposively sampled respondents. The findings—generated via multiple linear regression using IBM SPSS 26—unveil a compelling narrative: both content marketing and E-WOM exert a significant and positive impact on consumer intent to purchase. Beyond the numbers, this study unpacks a deeper truth: in the fast-paced arena of social commerce, relatable content and authentic digital conversations are not just tactics—they are the strategy.